Impact of the 'Healthy Youngsters, Healthy Dads' program on physical activity and other health behaviours: a randomised controlled trial involving fathers and their preschool-aged children - Philip J. Morgan; Jacqueline A. Grounds; Lee M. Ashton; Clare E. Collins; Alyce T. Barnes; Emma R. Pollock; Stevie-Lee Kennedy; Anna T. Rayward; Kristen L. Saunders; Ryan J. Drew; Myles D. Young (BMC, 2022)
Abstract Background Targeting fathers may be a key strategy to increase physical activity among their preschool-aged children, but limited research exists in this area. The primary study aim was to examine the impact of a lifestyle program for fathers and their preschool-aged children on child physical activity levels. Methods A total of 125 fathers (aged: 38 ± 5.4 years, BMI: 28.1 ± 4.9 kg/m2) and 125 preschool-aged children (aged: 3.9 ± 0.8 years, BMI z-score: 0.3 ± 0.9, 39.2% girls) recruited from Newcastle, Australia, NSW were randomised to (i) the Healthy Youngsters, Healthy Dads (HYHD) program, or (ii) wait-list control group. The program included two fathers-only workshops (2 h each) and eight father-child weekly educational and practical sessions (75 min each), plus home-based activities targeting family physical activity and nutrition. Assessments took place at baseline, 10-weeks (post-intervention) and 9-months follow-up. The primary outcome was the children's mean steps/day at 10-weeks. Secondary outcomes included: co-physical activity, fathers' physical activity levels and parenting practices for physical activity and screen time behaviours, children's fundamental movement skill (FMS) proficiency, plus accelerometer based light physical activity (LPA) and moderate-to-vigorous physical activity (MVPA), screen time and adiposity for fathers and children. Process measures included; attendance, satisfaction, fidelity and retention. Linear mixed models estimated the treatment effect at all time-points for all outcomes. Results Intention-to-treat analyses revealed a significant group-by-time effect for steps per day at 10-weeks (+ 1417, 95%CI: 449, 2384) and 9-months follow-up (+ 1480, 95%CI: 493, 2467) in intervention children compared to control. There were also favourable group-by-time effects for numerous secondary outcomes including fathers' physical activity levels, children's FMS proficiency, and several parenting constructs. No effects were observed for both fathers' and children's accelerometer based LPA or MVPA, co-physical activity, screen-time and adiposity measures. Process evaluation data revealed very high levels of satisfaction, attendance, retention, and intervention fidelity. Conclusion Engaging fathers in a lifestyle program is a promising strategy to increase physical activity among preschool-aged children. Additional benefits to fathers' physical activity levels, children's FMS proficiency and parenting practices further support the importance of engaging fathers to improve family health outcomes. Trial Registration Australian New Zealand Clinical Trials Registry: ACTRN12619000105145 . Registered 24/01/2019.